2021
DOI: 10.1177/20587384211048562
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between lipoprotein associated phospholipase A2 and central overweight status

Abstract: Objective: Being overweight is associated with an increased risk of diabetes mellitus, hypertension, and cardiovascular disease. Lipoprotein-associated phospholipase A2 (Lp-PLA2) can independently predict the risk of cardiovascular disease. This study is aimed to investigate whether Lp-PLA2 was associated with an overweight status. Methods: This was a cross-sectional study that enrolled 3760 Chinese adults (age, 18–50 years) who underwent medical examination department of Xiamen Chang-Gung Hospital (XCGH) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…There was a positive correlation between blood pressure and Lp‐PLA 2 , no correlation between Lp‐PLA 2 and BMI, and only a small positive correlation with waist circumference with previous research reporting similar results 57,90,91 . However, a strong correlation was reported between Lp‐PLA 2 and central obesity in a Chinese population 92 …”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…There was a positive correlation between blood pressure and Lp‐PLA 2 , no correlation between Lp‐PLA 2 and BMI, and only a small positive correlation with waist circumference with previous research reporting similar results 57,90,91 . However, a strong correlation was reported between Lp‐PLA 2 and central obesity in a Chinese population 92 …”
Section: Discussionsupporting
confidence: 63%
“…57,90,91 However, a strong correlation was reported between Lp-PLA 2 and central obesity in a Chinese population. 92 The negative correlation between systolic blood pressure and PAF may be expected as animal studies show PAF induces systemic hypotension 93,94 and in humans, some biological actions of PAF include inducing vascular hyper-permeability and hypotension. 95 The current study found a medium negative correlation between PAF and both waist circumference and BMI.…”
Section: Blood Pressure Bmi and Wcmentioning
confidence: 99%
“… 32 Another study suggests that subjects with a central overweight status have a greater Lp-PLA2 level than those with normal weight and a peripheral overweight status. 33 The results illustrate that the association between Lp-PLA2 and different obesity indicators and the potential mechanisms deserve further investigation.…”
Section: Discussionmentioning
confidence: 89%
“…32 Another study suggests that subjects with a central overweight status have a greater Lp-PLA2 level than those with normal weight and a peripheral overweight status. 33 The results illustrate that the association between Lp-PLA2 and different obesity indicators and the potential mechanisms deserve further investigation. Next, we found that the combination of hs-CRP and Lp-PLA2 levels was significantly correlated with metabolic unhealthy in non-obese subjects, and the significant association was still present even after was still exist even after being adjusted for multi-variables, suggesting that combined hs-CRP and Lp-PLA2 was an independent risk factor for metabolic unhealthy in non-obese subjects.…”
Section: Dovepressmentioning
confidence: 89%
“… 13 Similarly, a study conducted among adults showed a significant association between central obesity, represented by higher waist circumference, and Lp-PLA2 levels. 14 Hence, the correlation between waist circumference and Lp-PLA2 level may be applicable to all age groups. Additionally, our study found that WHtR had a significant association with Lp-PLA2 by gender.…”
Section: Discussionmentioning
confidence: 99%